Implementasi Lima Pilar Utama dalam Pengabdian Masyarakat Internasional untuk Meningkatkan Pendidikan Anak-Anak Pekerja Migran Indonesia di Malaysia: - - Debora Benedicta Roi; Nenin Astiti Ayunda (JURPIKAT, 2026)
Limited access to formal education and the threat of national identity degradation overshadow the children of Indonesian Migrant Workers (PMI) in Malaysia. This community service aims to describe the implementation of the International Community Service Program "Mangunsari Goes Abroad 2026" in enhancing educational access, character development, health, and learning motivation. The method employed was an Action-Oriented Approach combined with interactive community education. The results demonstrated significant improvements across all indicators: visual literacy increased to 85%, national insight jumped to 90%, health awareness (PHBS) reached 90%, character building reached 85%, and entrepreneurial skills rose to 85%. In conclusion, the multidimensional integration of the five core programs successfully bridges educational gaps, builds independent character, and fosters sustainable nationalism among migrant workers' children.